Statistical Peculiar Features of Surface Cracking on Flat Clay Samples of Plastic Moulding when Heated by Heat Flow - I. K. Ivanovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Results of 240 time determinations pertaining to investigation of surface cracking initiation on flat samples of moulding mass (80% of the Lukoml clay + 20% of granite screenings) of various thickness (1 ...4 cm) while being heated with intensive heat flow (~ 1 W/cm2) are given and analyzed in the paper.It has been shown that under such heating conditions thickness of a sample practically does not make any effect on cracking intensity. At the same time determination of time indices concerning cracking initiation prior to clay mass treatment in the vacuum-press in accordance with K.Pirson’s criterion does not correspond to the normal law of distribution of random indices and corresponds to this law after processing in vacuum-press and moulding of air-dried bricks that makes it possible to predict with great reliability an output of qualitative products.